Pemanfaatan Teknologi Big Data dan Cloud Computing dalam Meningkatkan Pelayanan Koperasi Syariah (Tinjauan Literatur) - Syaiful Amrial Khoir; Hadi Tanuji (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Digital transformation is one of the essential needs in the development of sharia cooperatives in the Industrial Revolution 4.0 era. Rapidly developing information technology requires microfinance institutions such as cooperatives to adapt, in order to remain competitive, efficient, and relevant in meeting the needs of their members. Two main technologies that play an important role in this transformation are big data and cloud computing. This article aims to examine in depth how the use of big data and cloud computing can support the digital transformation process in sharia cooperatives. Using a literature review approach from various scientific sources, this article analyzes the basic concepts, potential benefits, case studies, and challenges of implementing both technologies in the context of sharia-based cooperatives. The results of the study show that big data can improve data-based decision making, risk management efficiency, and personalization of services to members. Meanwhile, cloud computing provides flexibility, cost efficiency, and accessibility of cooperative information systems widely, even in areas with minimal IT infrastructure. However, the success of implementing this technology is greatly influenced by the readiness of human resources, digital infrastructure, and compliance with sharia principles. This article also provides practical recommendations and a further research agenda as a contribution to the development of technology-based sharia cooperatives.